2017
DOI: 10.3349/ymj.2017.58.1.195
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oxidized Regenerated Cellulose, SurgiGuard®, in Porcine Surgery

Abstract: PurposeAdequate hemostasis is important for postoperative outcomes of abdominal surgery. This study evaluated the hemostatic effects and accompanying histopathological changes of a novel oxidized regenerated cellulose, SurgiGuard®, during abdominal surgery.Materials and MethodsTen pigs underwent wedge resection of the spleen (1×1 cm) and liver (1.5×1.5 cm). The resected surface was covered with Surgicel® fabric or fibril type (Group A) or SurgiGuard® fabric or fibril type (Group B). Surgicel® and SurgiGuard® w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
(36 reference statements)
1
7
0
2
Order By: Relevance
“…It has recently been determined that greige cotton generates low levels of H 2 O 2 (5–50 micromolar). However, the mechanism of action of hydrogen peroxide production in the cotton fiber may be considered multifactorial, i.e., trace metals [ 15 , 16 ], polyphenols [ 15 , 17 ], peroxidase [ 17 ], super oxidase dismutase [ 18 , 19 ], and pectin [ 17 , 20 ], which are found in both brown and white cotton varieties, have been correlated with activity [ 15 ]. This study examines hydrogen peroxide production from unbleached cotton based on formularies prepared by simple modifications adoptable for dressing development.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been determined that greige cotton generates low levels of H 2 O 2 (5–50 micromolar). However, the mechanism of action of hydrogen peroxide production in the cotton fiber may be considered multifactorial, i.e., trace metals [ 15 , 16 ], polyphenols [ 15 , 17 ], peroxidase [ 17 ], super oxidase dismutase [ 18 , 19 ], and pectin [ 17 , 20 ], which are found in both brown and white cotton varieties, have been correlated with activity [ 15 ]. This study examines hydrogen peroxide production from unbleached cotton based on formularies prepared by simple modifications adoptable for dressing development.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al . 27 found no abscesses or infectious changes, nor signs of severe inflammation at microscopy when using oxidized regenerated cellulose in abdominal surgery in pigs. Yoon et al found similar results when investigating the use of oxidized regenerated cellulose in an animal model 28 .…”
Section: Discussionmentioning
confidence: 78%
“…[11,16] Other complications are coronary ischemia (due to periaortic compression) and nerve injury (compression when left in and around bony canals) due to its hygroscopic nature. [13][14][15][16][17] No patient in Group B suffered from any complications related to Surgicel®.…”
Section: Methodsmentioning
confidence: 97%